Different waves of effector genes with contrasted genomic location are expressed by Leptosphaeria maculans during cotyledon and stem colonization of oilseed rape. (25th August 2016) - Gervais, Julie; Plissonneau, Clémence; Linglin, Juliette; Meyer, Michel; Labadie, Karine; Cruaud, Corinne; Fudal, Isabelle; Rouxel, Thierry; Balesdent, Marie‐Hélène
Summary: Leptosphaeria maculans, the causal agent of stem canker disease, colonizes oilseed rape ( Brassica napus ) in two stages: a short and early colonization stage corresponding to cotyledon or leaf colonization, and a late colonization stage during which the fungus colonizes systemically and symptomlessly the plant during several months before stem canker appears. To date, the determinants of the late colonization stage are poorly understood; L. maculans may either successfully escape plant defences, leading to stem canker development, or the plant may develop an 'adult‐stage' resistance reducing canker incidence. To obtain an insight into these determinants, we performed an RNA‐sequencing (RNA‐seq) pilot project comparing fungal gene expression in infected cotyledons and in symptomless or necrotic stems. Despite the low fraction of fungal material in infected stems, sufficient fungal transcripts were detected and a large number of fungal genes were expressed, thus validating the feasibility of the approach. Our analysis showed that all avirulence genes previously identified are under‐expressed during stem colonization compared with cotyledon colonization. A validation RNA‐seq experiment was then performed to investigate the expression of candidate effector genes during systemic colonization. Three hundred and seven 'late' effector candidates, under‐expressed in the early colonization stage and over‐expressed in the infected stems, were identified. Finally, our analysis revealed a link between the regulation of expression of effectors and their genomic location: the 'late' effector candidates, putatively involved in systemic colonization, are located in gene‐rich genomic regions, whereas the 'early' effector genes, over‐expressed in the early colonization stage, are located in gene‐poor regions of the genome.